2021
DOI: 10.46419/vs.52.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of single nucleotide polymorphisms (SNPs) in HER2, MUC1, ESR1, and BRCA1 genes associated with canine mammary cancer

Abstract: Worldwide, canine mammary cancer (CMC) is the most frequent type of neoplasia in female dogs, and it is three times more frequent in dogs than in humans. In Colombia, CMC is the second most frequent type of cancer, after skin neoplasia. Genetics is one of the most important factors in- volved in any type of cancer, and the genetic ba- sis of this disease is reflected through line breed- ing due to changes in allelic frequencies that are traceable using molecular markers. This study aimed to detect single nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In HBC, known mutations of MUC-1 gene occurs as somatic changes within tumor genome [ 32 ]. On one hand, Carvajal-Agudelo et al [ 33 ] found three single-nucleotide polymorphisms (SNPs) and two deletions (one in exon 7 and one in intron 6) in canine MUC-1. Furthermore, Carvajal-Agudelo et al [ 33 ] found no significant correlation between MUC-1 expression and tumor grade or tumor type among CMTs; they found no correlation between MUC-1 and CMT incidence [ 33 ].…”
Section: Gene and Protein Structure Of Mucin-1mentioning
confidence: 99%
See 2 more Smart Citations
“…In HBC, known mutations of MUC-1 gene occurs as somatic changes within tumor genome [ 32 ]. On one hand, Carvajal-Agudelo et al [ 33 ] found three single-nucleotide polymorphisms (SNPs) and two deletions (one in exon 7 and one in intron 6) in canine MUC-1. Furthermore, Carvajal-Agudelo et al [ 33 ] found no significant correlation between MUC-1 expression and tumor grade or tumor type among CMTs; they found no correlation between MUC-1 and CMT incidence [ 33 ].…”
Section: Gene and Protein Structure Of Mucin-1mentioning
confidence: 99%
“…On one hand, Carvajal-Agudelo et al [ 33 ] found three single-nucleotide polymorphisms (SNPs) and two deletions (one in exon 7 and one in intron 6) in canine MUC-1. Furthermore, Carvajal-Agudelo et al [ 33 ] found no significant correlation between MUC-1 expression and tumor grade or tumor type among CMTs; they found no correlation between MUC-1 and CMT incidence [ 33 ]. On the other hand, Manuali et al showed that in CMT, MUC-1 expression is positively related to tumor grade; high MUC-1 in serum is found in grade II and III [ 24 , 34 ].…”
Section: Gene and Protein Structure Of Mucin-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Over-expression of MUC-1 was found in many cancers and was related to increased tumor invasiveness and poor prognosis [ 39 , 40 ]. Gene mutations, such as two deletions (in intron 6 and exon 7) and three single-nucleotide polymorphisms, were found in canine MUC-1 [ 41 ]. In CMTs, MUC-1 expression was also associated with tumor invasion and the presence of metastases, which had prognostic significance [ 22 , 42 , 43 ].…”
Section: Canine Mammary Tumorsmentioning
confidence: 99%
“…In these cases, there is an evident deterioration of the animal’s health due to the progress of the disease, and deciding to prolong the animal’s life could lead to dysthanasia (painful and agonic death) [ 41 , 60 ]. When considering patients with oncological diseases, prognostic indicators such as mitotic indices (e.g., argyrophilic nucleolar organizer regions, Ki-67, and proliferating cell nuclear antigen) [ 61 ], nucleotide polymorphisms in HER-2/neu, BRCA1, and P53 genes [ 62 ], and levels of E-cadherin expression [ 63 ] as markers of tumor grade and metastatic process in mast cell tumors, mammary cancer, and squamous cell carcinomas should be taken into account. In dogs with lymphoma, positive B-markers (CD20, CD21, CD79a, CD3, CD5, and PAX5) are used to diagnose and classify the tumors [ 64 , 65 ].…”
Section: Ethical Implications Of Euthanasia In Companion Animalsmentioning
confidence: 99%